FORMATION OF A STRATEGIC-ORIENTED MANAGEMENT SYSTEM BASED ON KEY PERFORMANCE INDICATORS (Development Service Industry Management, 2024)
The formation of a strategically oriented management system is critically important for ensuring the effective and efficient operation of modern organizations. The purpose of the article is the systematization of experience and the development of practical recommendations regarding the features of using the system of key performance indicators for the formation of a strategic-oriented approach to the management of the organizationThe article examines the theoretical and applied aspects of developing a strategic management system based on key performance indicators. The prerequisites and the need for the development of the specified management system have been defined and substantiated, which allows to increase the manageability of the organization with the help of quantitatively measurable and effective performance indicators, taking into account the identified cause-and-effect relationships and the coherence of the actions of both individual structural units and individual performers.A model for the development and implementation of a strategically oriented management system based on key performance indicators is proposed, which allows, following a defined sequence of actions, to ensure the achievement of the organization's goals. Examples of implementation of the proposed system for a trade enterprise are given. Blocking factors for the implementation of the system of key performance indicators are defined and presented in the form of an Ishikawa diagram, which are grouped into six main blocks: market, finance, business processes, personnel development, personnel evaluation, and corporate culture. The benefits of using a system of key performance indicators for modern organizations are covered in detail.
Keywords: management; management system; strategic management; key performance indicators